Learning by discovery in systems of special points and lines in a triangle - Joya, Carlos Alberto; Suárez, Publio (Universidad Pedagógica y Tecnológica de Colombia, 2020)
The article presents the results of a research about learning the special elements in a triangle in Euclidean geometry, carried out with tenth grade students of a school in Tunja, aged between 14 and 17. The conjecturing and the characterization of these elements were analyzed based on the exploration of dynamic geometry environments designed in GeoGebra. The methodology was qualitative with descriptive-interpretative characteristics. The proposal is based on Bruner’s learning by discovery approach. The students progressed in their intuitive thinking by implementing activities focused on visualization, mediated by dynamic drawings. The results show that students learned about special lines and points in a triangle: they identified these in the graphic representation, prioritized the use of natural language, conjectured about their properties and discovered relations and properties in triangles; which caused significant learning. Thus, they advanced in the development of spatial thinking. An important element was the development of the students’ digital competence with the use of GeoGebra.